An extrapolation method to determine the effective notch stress in circular hollow section X‐joints. Issue 2 (19th May 2016) - Pradana, M. R.; Qian, X.; Swaddiwudhipong, S.; Shen, W.
Abstract: This paper presents an extrapolation method to determine the effective notch stress (ENS) on the weld toes of welded circular hollow section (CHS) X‐joints in‐line with the extrapolation method to determine the structural hot‐spot stress in existing design guidelines. This investigation verifies and extends the recently proposed ENS extrapolation scheme to CHS X‐joints, which elevates significantly the difficulty in generating a weld toe radius along the brace‐to‐chord intersection as required in existing guidelines. An extensive numerical study then investigates the ENS extrapolation for CHS X‐joints under three loading conditions, namely, the brace axial load, the brace in‐plane bending load, and the brace out‐of‐plane bending load. The numerical study derives a set of recommended extrapolation parameters that ensures accurate ENS estimation for each loading condition. This paper demonstrates that the proposed extrapolation method for the CHS X‐joints yields good agreement with the standard ENS calculation procedure described in the International Institute of Welding (IIW) guideline.